The genome sequence of the Oak-tree Pug, Eupithecia dodoneata (Guenée, 1858) - Boyes, D; Holland, PWH (F1000Research, 2023)
We present a genome assembly from an individual male Eupithecia dodoneata (the Oak-tree Pug; Arthropoda; Insecta; Lepidoptera; Geometridae). The genome sequence is 353.7 megabases in span. Most of the assembly is scaffolded into 31 chromosomal pseudomolecules, including the assembled Z sex chromosome. The mitochondrial genome has also been assembled and is 15.3 kilobases in length.